National Institute of Public Health/School of Public Health of Mexico: contributions to social equity and knowledge-based public policies - Eduardo Lazcano-Ponce (Instituto Nacional de Salud Pública, 2022)
The School of Public Health of Mexico (ESPM, in Spanish), was founded on March 23, 1922, several years after the creation of the first schools of public health in the United States of America (USA), such as Johns Hopkins in 1916 and those of Harvard, Yale, and Columbia, among others. The Escuela de Salubridad, as the ESPM was initially called, was the first of its kind in Latin America and the fifth in the world; thus, it was responsible for providing the first public health degrees in Mexico to medical health officers and other higher education diplomas in the fields of hygiene and public health. Several years after its own founding, in 1987, the ESPM co-founded the National Institute of Public Health (INSP, in Spanish) which to date continues to be the organization in which the ESPM is housed. Since the ESPM merged with the INSP, research and human resources training have been considered necessary processes for initiating and strengthening structural change in the field of health at the national and regional levels. As part of its centennial, the ESPM is committed to the continued expansion of its future perspective through the restructuring of its academic programs; this is a process in which the instilling of values, a unified curriculum based on public health, a flexible educational model and social commitment are fundamental. Key words: Public Health, Public Health School of Mexico, social equity and education.